2018
DOI: 10.3892/etm.2018.5708
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effects of hydroxychloroquine and artemisinin combination therapy via the nuclear factor‑κB signaling pathway in lupus nephritis mice

Abstract: Lupus nephritis (LN) is one of the most common and severe manifestations of systemic lupus erythematosus, leading to permanent renal damage and chronic kidney disease. Hydroxychloroquine (HCQ) serves a protective role against lupus-associated clinical manifestations and medical complications; however, it results in numerous adverse reactions, limiting its long-term use. The aim of the present study was to investigate the combined effect of HCQ and artemisinin (ART) on LN, and to elucidate the underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Hydroxychloroquine, which was initially touted as the wonder drug and used in many regimens for the treatment of COVID-19, has fallen off from popularity due to its cardiac toxicity. It reduces the levels of TNF-α, TNF-1β, IgG and IFN-γ, which in turn blocks the NF-κB pathway (Liang et al 2018 ). Inhaled nitric oxide (NO) may be useful in the management of COVID-19 ARDS, and there is growing evidence that it reduces the inflammatory cell-mediated lung injury by inhibiting neutrophil activation and subsequent pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxychloroquine, which was initially touted as the wonder drug and used in many regimens for the treatment of COVID-19, has fallen off from popularity due to its cardiac toxicity. It reduces the levels of TNF-α, TNF-1β, IgG and IFN-γ, which in turn blocks the NF-κB pathway (Liang et al 2018 ). Inhaled nitric oxide (NO) may be useful in the management of COVID-19 ARDS, and there is growing evidence that it reduces the inflammatory cell-mediated lung injury by inhibiting neutrophil activation and subsequent pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…For LN mice, it has been reported that treatment with ARSs could decrease interferon-gamma (IFN-g), tumor necrosis factor-alpha (TNF-a), interleukin-6 (IL-6) in serum, and blocked intercellular adhesion molecule-1 (ICAM-1), fractalkine, NF-kB signaling pathway in renal (Dong et al, 2003;Li et al, 2006;Wang et al, 2010;You et al, 2014;Liang et al, 2018). A similar effect was observed in the nephritis and septic AKI models Wan and Li, 2017;Liu et al, 2019).…”
Section: In Vivomentioning
confidence: 99%
“…Previous studies have shown that KLF15 can block the interaction of nuclear factor NF-κB p56 with the co-activator P300 by directly interacting with P300, and subsequently by inhibiting the P300-p56-activated inflammatory pathway 42. The most recent evidence has indicated that KLF15 can improve LN 21. A combined treatment of Hydroxychloroquine and artemisinin in LN may exert renal-protective effects by increasing expression levels of KLF15, leading to a decrease in the levels of its downstream target, NF-κB, and consequently suppressing the inflammatory response 21.…”
Section: Roles Of Klf15 In Kidney Diseasementioning
confidence: 99%
“…Moreover, KLF15 was also involved in metabolic dysfunctions, including diabetes, inflammation, obesity, and cardiac hypertrophy 17-20. Recently, a growing number of studies have indicated that KLF15 is implicated in renal physiological processes and pathologic progression of CKD, involving podocyte differentiation, tubular physiology, mesangial pathology, and renal fibrosis 12, 13, 16, 21. An improved understanding of CKD and its molecular mechanisms will enable further research into new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%